2018
DOI: 10.1128/msystems.00211-17
|View full text |Cite
|
Sign up to set email alerts
|

Omics-Based Insights into Flavor Development and Microbial Succession within Surface-Ripened Cheese

Abstract: Fermented foods, in particular, surface-ripened cheese, represent a model to explain the metabolic interactions which regulate microbial succession in complex environments. This study explains the role of individual species in a heterogeneous microbial environment, i.e., the exterior of surface-ripened cheese. Through whole-metagenome shotgun sequencing, it was possible to investigate the metabolic potential of the resident microorganisms and show how variations in the microbial populations influence important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 57 publications
2
78
0
1
Order By: Relevance
“…With the fermentation process, the bacterial metabolism tended to be vigorous, like lipolysis and proteolysis (Zheng et al., ), provided the sensorial features in fermentation process of Kedong sufu. And the strong flavor, which comes from the bacterial biochemical metabolism, predicated the gradual maturation of fermented food (Bertuzzi et al., ). Figure shows the percent content of each volatile compound in Kedong sufu during fermentation process.…”
Section: Resultsmentioning
confidence: 99%
“…With the fermentation process, the bacterial metabolism tended to be vigorous, like lipolysis and proteolysis (Zheng et al., ), provided the sensorial features in fermentation process of Kedong sufu. And the strong flavor, which comes from the bacterial biochemical metabolism, predicated the gradual maturation of fermented food (Bertuzzi et al., ). Figure shows the percent content of each volatile compound in Kedong sufu during fermentation process.…”
Section: Resultsmentioning
confidence: 99%
“…; Bertuzzi et al . ). Degradation of BCAAs provides CNS with branched‐chain fatty acids for their cell membrane biosynthesis, whereby the first step consists of the production of α ‐keto acids by aminotransferases (Beck et al .…”
Section: Strengthsmentioning
confidence: 97%
“…In cheese, conventional use focuses almost exclusively on flavour (Bertuzzi et al . ) but can as well affect colour in smear cheeses (Bertuzzi et al . ).…”
Section: Opportunitiesmentioning
confidence: 99%
“…Dimethyl disulphide and its precursor, methanethiol, have been shown to be correlated to the presence of G . candidum in situ (Bertuzzi et al, ). Boutrou and Gueguen () found the following sensory attributes to be characteristic of G .…”
Section: Role Of Yeasts In Cheese Ripeningmentioning
confidence: 99%
“…lipolytica ) had greater potential (Padilla, Belloch, et al, ; Sørensen, Gori, Petersen, Jespersen, & Arneborg, ). Bertuzzi et al () showed that both carboxylic acids originating from lipolysis and alcohols originating from leucine and fatty acid oxidation were correlated to the presence of D . hansenii on the cheese surface.…”
Section: Role Of Yeasts In Cheese Ripeningmentioning
confidence: 99%